.NET Core microservices - Gankiewicz, Piotr (Packt, 2017)
"Microservices are an architectural style that promotes the development of complex applications as a suite of small services based on business capabilities. This course will help you identify the appropriate service boundaries within the business. We'll start by looking at what microservices are, and their main characteristics. We will develop a basic distributed system using the microservice architecture and tools such as RabbitMQ service bus, to send messages across the separated services, or MongoDB, which is a NoSQL database. Within the course, we will focus on creating the HTTP API to act as a gateway to the whole system and so-called Activities Service, responsible for handling the incoming messages (or actually the commands that will be distributed through the services bus). We'll also implement the Identity Service, which will serve JSON Web Tokens (JWT) to authenticate requests incoming to the API. Our application will let the user store information about the activities performed at a given date for a selected category, for example, work, tasks, sport, and so on. Once the request to save the activity is published within the system, the Activities Service will handle the business logic and decide whether the activity is valid, which will eventually result in publishing the event about processing the successful or rejected activity. In the course, you will also learn about commands and events as well as handlers which is one of the most popular design patterns when it comes to creating distributed systems. By the end of the course, your services will be built using ASP.NET Core framework and later on, you will use tools such as Docker and Docker Compose to pack your application into the container and deploy it to the virtual machine running in the cloud."--Resource description page